Development of auto-calibrated interfacing circuit for thick film multi-gas sensor - Khakpour, Reza (2010)
The gas sensors have been used for a number of applications particularly for reducing the pollution and human exposure to dangerous gasses. There are different ways of fabricating gas sensor which typically have high accuracy and high ability. One of these methods is by using thick film technology. Due to their high sensitivity and low cost of production, thick film gas sensors have been extensively employed. Screen printing is the general method of manufacturing thick film gas sensors which is a well organized technology and a low-cost way for large-scale production. The gas sensor with thick film technology consists of a sensitive layer and a heater. Each gas sensor is biased at constant temperature where the best reaction occurs at this temperature, which means they need be controlled. The effect of ambient temperature must be compensated because they will influence the heater performance negatively. The main objective of this thesis is to drive the heaters of thick film multi gas sensors by controlling the voltage and keeping the temperature of the heaters constant so that each heater will be able to compensate the effect of ambient temperature changes. Furthermore, the system can measure, monitor and display the gases detected by multi sensors in wide range. The interface circuit consists of ADC, DAC, microcontroller, current buffer, and latch buffer. The voltage divider method was used in this thesis by employing external series resistor in order to control the heater, compensate the ambient temperature, and measure the gas. Finally, a single microcontroller was employed to automatically run the entire process such as driving the heaters, controlling the heaters temperature, compensating the ambient temperature of the heaters, measuring the amount of gasses detected by the sensors and finally selecting the sensors.